Analisis Kurikulum Bahasa Arab Berbasis 4C (Critical Thinking, Communication, Collaboration, Creativity) untuk Pengembangan Kompetensi Abad 21 pada Siswa - Muhammad Tareh Aziz; Laili Mas Ulliyah Hasan; Muhammad Rido’i (Pascasarjana Universitas Qomaruddin, 2024)
In the 21st century, critical thinking skills, effective communication, collaboration, and creativity are essential in learning. The objective of this study is to scrutinize the Arabic language curriculum, which employs the 4C approach to enhance language proficiency and cultivate students' future-ready character traits. We designed this study using a qualitative descriptive method, collecting data through observation, interviews, and document analysis. The results of the study show that the integration of the 4Cs in the Arabic curriculum helps students master language competencies that are more contextual and relevant to daily life, especially in 21st century skills. Additionally, the challenge lies in developing human resources to effectively implement this approach.